Tree-ring management take the long view and grow your business slowly - Tsukakoshi, Hiroshi 1937- (Japan library (Shuppan Bunka Sangy?o Shink?o Zaidan), 2015)
"Hiroshi Tsukakoshi is the chairman of a kanten manufacturer that is far from the bustle of Tokyo amid the natural beauty of Nagano prefecture. His desire has been to build the kind of company that makes its employees happy and makes a contribution to society by doing so. His philosophy is to take the long view, growing his business slowly and steadily through "tree-ring management." "Over the last 20 years, no one has left the company because they were unhappy," Tsukakoshi declares. His unique management principles include such ideas as "rapid growth is the enemy" and "the essence of management is creating fans." His approach has resulted in rising sales and profits for half a century since the company's founding, and his company welcomes a steady stream of visiting executives and analysts from major corporations, including Murata Manufacturing and the Toyota Group. Chairman Tsukakoshi's philosophy of seeking steady growth over the long term will enlighten businesspeople around the world about a better way to manage corporations." -- Publisher's description.